Evaluation of the use of verses and Hadith during theoretical training in medical education - Aram Tirgar; Yasaman Habibzadeh; Zahra Refahi (Shahid Beheshti University of Medical Sciences, 2016)
For downloading the full-text of this article please click here. Background and Objectives: Since the beginning of the descent up to now, Quran was the endless source of Islamic sciences and the core of religious education.In addition, statements and deeds of the Prophet and the great Imams of Muslims are the other sources of life pattern. The aim of this study was to determine how to use the verses and Hadith during theoretical training in medical education. Materials and Methods: This cross-sectional study was conducted among all theoretical classes in a paramedical faculty. The data were collected by means of a tailor-made data collection sheet. The data in all classes were gathered through trained students for instructors. Having one third of classes during a semester was one of the inclusion criteria for each instructor. Results: The results of 900 sessions of 92 classrooms of the 7 major and 58 instructors of the Faculty of Paramedical Sciences showed that verses and Hadith were used at least once in 81 and 99 sessions, respectively. They were also used more than once in 17 and 22 classes.Totally, according to the results, the frequency distribution of the use of verses and Hadith was similar for male and female instructors. Conclusion: Despite using the verses and Hadith via considerable number of instructors during theoretical sessions, but more than half of instructors have never used such valuable messages. Therefore, the use of verses and hadiths according to the training subject is recommended. Keywords:  Research in Education, Quran, Verses, Hadith, Medical education For downloading the full-text of this article please click here.